Zooplankton community structure of Sungai Lukut and its estuary, Negeri Sembilan / Siti Fairus Musa - Musa, Siti Fairus (2016)
The zooplankton community structure of Sungai Lukut, Negeri Sembilan was studied between February to April 2015. Sampling stations included the river mouth, middle reaches and upper reaches of the river. Sampling was conducted utilizing a tow net with a 140 µm-mesh and a ring bridle with a 30 cm mouth diameter. The zooplankton sampling was conducted during floods and ebbs for both spring and neap tides. In situ salinity ranged from 9.21 to 35.59 parts per thousand; dissolved oxygen ranged from 2.99 to 8.57mg/1; temperature ranged from 28.63°C to 32.67°C and pH ranged from 6.61 to 9.87. Zooplankton density was significantly different (p<0.05) between rivermouth (47976±4025ind/m3), middle reaches (36647±5948ind/m3) and the upper reaches (27652±4425ind/m3) sampling Sims, Mean zooplankton density during neap tide was 63200±14874ind/m3 and 49042±21874ind/m3 during spring tide; 26826±7251ind/m3 during floods and 29478±11764ind/m3 during ebbs. Sampling site, tide and phase of tide showed significant difference for water physicochemical parameters (p<0.05), Shannon‘s H‘ ranged from 1.87 (upper reaches) to 2.26 (river mouth); Margalef‘s d ranged from 5.58 (river mouth) to 5.68 (middle reaches): and Pielou‘s J’ ranged from 0.63 (upper reaches) to 0.74 (middle reaches). Shannon‘s index, Margalef‘s richness and Pielou‘s evenness was higher during spring tide (H’:2.19, d=5.27, J‘=0.74); Shannon‘s index and Pielou’s evenness was higher during ebbs: (H':2.15, J‘:0.75) while Margalef‘s richness was higher during floods (d=5.7). PCA ordinations showed most of the zooplankton were found at all sampling site with difference abundance while CCA ordination showed distribution and abundance of zooplankton were more affected by salinity, pH and dissolved oxygen.